Macroeconomic Impact of International Reserves: Empirical Evidence from South Asia - Shrestha, Prakash Kumar (NRB Economic Review, 2016)
In recent years, many emerging countries have been accumulating substantial amount of international reserves by outpacing traditional benchmark in response to a series of financial crises in the world. In this context, this paper constructs a dynamic macro model with new monetary policy rule to examine the implications of international reserve accumulation for macroeconomic outcomes such as economic growth and inflation. Such a macro model is empirically examined in the data of South Asian countries, namely Bangladesh, India, Nepal, Pakistan and Sri Lanka by using Panel VAR method for the period of 1990-2014. The empirical results show that increase in international reserves tends to cause higher economic growth in these countries but without significant impact on inflation. This implies that these countries can move further utilizing the accumulated international reserves productively which will enhance economic growth and maintain internal and external balances.